The Impact of Complete Revascularization in Symptomatic Severe Left Ventricular Dysfunction between Coronary Artery Bypass Graft and Percutaneous Coronary Intervention - Hsiu-Yu Fang; Yen-Nan Fang; Yin-Chia Chen; Jiunn-Jye Sheu; Wei-Chieh Lee (Cardiology Research and Practice)
Objective. The study aimed to compare the clinical outcomes between the patients receiving coronary artery bypass surgery (CABG) or percutaneous coronary intervention (PCI) for the patients with symptomatic severe left ventricular (LV) dysfunction and coronary artery disease (CAD). Methods. Between February 2007 and February 2020, a total of 745 patients who received coronary artery angiography for reduced LV ejection fraction (LVEF) < 40% and symptomatic New York Heart Association (NYHA) functional class ≥ 3 were recruited. The patients (N = 236) who were diagnosed with dilated cardiomyopathy or valvular heart disease without coronary artery stenosis, those with prior history of CABG or valvular surgery (N = 59), those who presented ST-segment elevated myocardial infarction (STEMI), those with a CAD and SYNTAX score of  ≦ 22 (N = 175), those who received emergent CABG for coronary perforation (N = 3), and those who had NYHA class ≦ 2 (N = 65) were excluded. Finally, 116 patients with reduced LVEF and those who had a SYNTAX score >22, who received CABG (N = 47) and PCI (N = 69), were recruited for this study.Results. There was no significant difference in the incidence values of in-hospital course and those of in-hospital mortality, acute kidney injury, and postprocedural hemodialysis. There was no significant difference in the 1-yearfollow-up of recurrent MI, revascularization, or stroke between the groups. The 1-year heart failure (HF) hospitalization rate was significantly lower in the CABG group than in all patients of the PCI group (13.2% vs. 33.3%; p=0.035); however, there was no significant difference in the same variable between the CABG group and the complete revascularization subgroup (13.2% vs. 28.2%; p=0.160). The revascularization index (RI) was significantly higher in the CABG group than in all patients of the PCI group or complete revascularization subgroup (0.93 ± 0.12 vs. 0.71 ± 0.25; p<0.001) and (0.93 ± 0.12 vs. 0.86 ± 0.13; p=0.019). The 3-year HF hospitalization rate was significantly lower in the CABG group than in all patients of the PCI group (16.2% vs. 42.2%; p=0.008); however, there was no difference in the same variable between the CABG group and the complete revascularization subgroup (16.2% vs. 35.1%; p=0.109). Conclusions. In patients with symptomatic (NYHA class ≥ 3) severe LV dysfunction and CAD, CABG brought less HF admission when compared to patients in the PCI group, but this did not differ when compared to the complete revascularization subgroup. Therefore, an extensive revascularization, achieved by CABG or PCI, is associated with a lower HF hospitalization rate during the 3-yearfollow-up period in such populations.